Social Representations About Teaching in Higher Education Have the Teaching Staff of Two Mexican Public Universities - Escalante-Ferrer, Ana Esther (2021)
This paper derived from a broader joint investigation. It aims to consolidate research through social representations and, particularly, to expose social representations that a group of Mexican university professors has built about teaching in higher education, an activity inherent to their daily work in academic spaces. This group is attached to the Autonomous University of Morelos and the University of Colima. A qualitative research approach was designed to obtain the teaching representations. For this purpose, a semi-structured interview guide, with expert judging, was applied to 16 teachers selected by intentional sampling. The information was processed with the Atlas.ti software. As an analysis technique of the discursive corpus obtained, an interpretative approach of the social representations was used; it was conducted according to Cuevas’ scheme (2016) that recovers some elements of the stages based on Taylor & Bogdan (1987/1992). The findings of the study reflect the following four social representations: teaching as a profession with (and requiring) vocation; teaching as a satisfactory activity due to the transcendence of the school and its socio-professional importance; teaching as an inherent (and not preferred) task to the activity of the research professor; and teaching as a field of training and lifelong learning. We conclude that the social representations on teachers’ teaching show generalities and particularities according to their different work and training careers in the institution.